The Effect of Temperature on Gonadal Sex Differentiation of Yesso Scallop Patinopecten yessoensis - Liu, Tian; Li, Ruojiao; Liu, Liangjie; Wu, Shaoxuan; Zhang, Lijing; Li, Yajuan; Wei, Huilan; Shu, Ya; Yang, Yaxin; Wang, Shi; Xing, Qiang; Zhang, Lingling; et al. (Frontiers in Cell and Developmental Biology, 2022)
Many marine organisms are generally poikilotherms, making seawater temperature one of the most important environmental factors affecting gonadal sex differentiation. Mollusca is the second-largest animal phylum with diverse reproductive systems, but studies on the impact of temperature on sex differentiation are limited to a few sequential hermaphrodites. By combining morphological and molecular analyses, we investigated the effect of temperature on gonadal sex differentiation of a commercially important gonochoristic scallop Patinopecten yessoensis in the field and under laboratory conditions. Based on the relative expression of FoxL2 and Dmrt1L in the gonads of 6- to 12-month-old scallops, we found the scallops start to differentiate at 21℃. To eliminate the effect of factors other than temperature on sex differentiation, we compared the gonadal development of juvenile scallops at different temperatures (21℃, 16℃ and 11℃) under laboratory conditions. After 50 days of treatment, the 11℃ group contain more germ cell types, and have higher sex differentiation rates than the 21℃ group. But no obvious sex bias was observed. These results suggest that high temperature (21°C) inhibits sex differentiation, whereas low temperature (11℃) accelerates sex differentiation by 2 months for this cold-water species. It also supports juvenile P. yessoensis is gonochoristic rather than protandrous hermaphroditic. Our study addresses for the first time an environmental influence associated with genetic controls on scallop sex differentiation. It will facilitate a better understanding of how environmental factors affects gonadal development in poikilotherms, especially in the less studied molluscs.